Investigating the Hydraulic Behaviours of an Alluvial Meandering River Reach Between Two Barrages - Zainab D. Abbass; Jaafar S. Maatooq; Mustafa M. Al-Mukhtar (Civil Engineering Journal, 2024)
The Abassia-Shammia is a meandering stream in Najaf province. Predicting and estimating the flow behavior of meandering rivers is crucial for designing hydraulic structures in an accurate manner in the vicinity and conducting environmental and ecological studies. The hydraulic properties of an alluvial stream are typically subject to change due to its location between two barrages. In this study, HEC RAS 2D, developed by the Hydrologic Engineering Center’s River Analysis System, was employed to simulate the hydraulic performance of the Euphrates River reach between two series of barrages, i.e., Abbassia and Shammia. Reliable input data, such as Digital Elevation Models (DEMs), land cover classification, and data for the 2023 hydrograph as a boundary condition, were utilized to develop the hydraulic model. The model was calibrated by using the observed water surface elevation from field measurements downstream of Abbassia to match the ones calculated by the model. Hence, the hydraulic model of the Euphrates River was created using an appropriate Manning roughness coefficient value (n = 0.04) based on the most suitable values of statistical indices, correlation coefficient (R²), and root mean squared error (RMSE) to assess the agreement between the observed and simulated data throughout the calibration and validation phases. To visualize the HECRAS2D output, the hydraulic maps for the study region were presented. The ten cross-sections from the field study (investigated at the same period of flow hydrograph) were presented for modeling to emphasize the river's hydraulic behaviors. Based on the results, the water surface elevation ranged between 19.1–29.2 m.a.s.l., and the flow velocity was 2.50 m/s. Meanwhile, the values of bed shear stress (Pa) and the water depth (m) ranged between 0.1 Pa and 8.93 m for the entire river. The results also proved the superiority of the HEC RAS2D model to reliably represent the hydraulic performance of the Euphrates River reach located between the two barrages. Doi: 10.28991/CEJ-2024-010-05-013 Full Text: PDF